Extracorporeal Methods of Hemocorrection in Patients with Abdominal Sepsis - O. V. Nikitina; S. I. Rey; Y. V. Zabrodskaya; V. I. Avfukov; A. G. Lebedev; P. A. Yartsev; G. A. Berdnikov; A. M. Kaziyeva; E. A. Ostrogina (Неотложная медицинская помощь, 2024)
BACKGROUND. Theoretical data convincingly support the use of extracorporeal hemocorrection (ECHC) methods in the treatment of sepsis. However, a large number of researchers have still not been able to convincingly prove the advantage of ECHC methods; there is no unanimity of opinion. We tried to analyze our own experience in using ECHC methods in the treatment of abdominal sepsis over the past 3 years.   AIM OF STUDY. To analyze the use of ECHC methods in the early stages of treatment of abdominal sepsis, to determine whether their use had an advantage for survival.   STUDY DESIGN. Prospective cohort.   DESCRIPTION OF THE METHOD. In 50 cases (group 1), ECHC was performed early after surgery. The median time from admission to the intensive care unit after surgery to the start of ECHC was 25.3 (17.7; 36.5) hours. When determining the ECHC modality, we were guided by the individual approach and clinical experience of the ECHC specialist. Apheresis methods alone were performed in 8 % of patients (4/50), a combination of apheresis methods and renal replacement therapy was performed in 40 % (20/50), renal replacement therapy (RRT) methods were performed in 98 % (46/50), plasmapheresis/plasma exchange/selective plasma filtration were performed in 30 % (15/50), selective hemosorption of cytokines was performed in 4 % (2/50), selective hemosorption lipopolysaccharides was performed in 24 % (12/50). We analyzed outcomes, assessments of the severity of functional disorders and sepsis-associated organ dysfunction according to the APACHE scales II and SOFA and their dynamics, probabilities of outcomes depending on the scores on the indices (logistic regression); life times, cumulative survival rate (Kaplan-Meier method).   SAMPLE CHARACTERISTICS. There were 113 patients after emergency laparotomy due to widespread peritonitis, abdominal sepsis, aged from 23 to 90 years. 67 men, 46 women. In 50 cases of observation (group 1), ECHC was performed in the early stages ; in 63 cases, methods of active hemocorrection were not used (group 2). In group 1 there were 35 patients with septic shock and 15 patients with stable hemodynamics (subgroup 1/shock and subgroup 1/sepsis). In group 2 there were 20 patients with shock and 43 with stable hemodynamics (subgroup 2/shock and subgroup 2/sepsis).   RESEARCH RESULTS ECHC. Methods allowed survival of patients with more severe APACHE scores II and SOFA: in survivors in subgroup 1/shock Me 29 (24; 31) versus 23 (14; 26) in the subgroup 2/shock and 8 (4; 10) versus 4 (2; 6) points, p=0.048 and p = 0.010; with stable hemodynamics in survivors in subgroup 1/sepsis Me 20 (17; 22) versus 15 (11; 19) in subgroup 2/sepsis, p=0.016. ECHC changed the survival threshold in favor of more severe patients from 29 to 33 points; reduced the likelihood of an unfavorable outcome 1.2-fold for each point on the APACHE scale II and 1,276 times over the entire range of estimates; prolonged survival time in hemodynamically unstable patients at a significance level of p = 0.083, shifting the first quartile of survival from 1 to 12 days, the median from 12 to 20, the third quartile from 27 to 45 days. When performing ECHC, the cumulative survival rate was higher throughout the entire hospital observation period: 0.886 (95 % CI 0.780–0.939) in 2 days versus 0.700 (95 % CI 0.499–0.802); 0.800 (95 % CI 0.667–0.868) in 10 days versus 0.545 (95 % CI 0.325–0.658); 0.653 (95 % CI 0.494–0.734) in 14 days versus 0.416 (95 % CI 1.185–0.533). Overall mortality from all causes was 35.4 % (40/113), 67.3 (37/55) with shock, 5.2 % (3/58) with stable hemodynamics. The maximum risk of an unfavorable outcome occurred in the early stages: 30 % (12/40) of all deaths occurred in the first 4 days after surgery, 20 % (8/40) in the first 24 hours. In shock patients, 10-day mortality was lower when performing ECHC: 20.0 % (7/35) versus 45.0 % (9/20), p = 0.050, 1st stage. Fisher’s test, P = 0.38 insufficient. Hospital mortality in the shock subgroups was equal, all the advantages of ECHC achieved in the early stages were lost; although in most late outcomes the peritonitis was relieved; which was confirmed during the section.   CONCLUSIONS. The power of the study was sufficient to identify statistically significant advantages of extracorporeal hemocorrection in the treatment of abdominal sepsis based on APACHE index estimates II and SOFA. For the Kaplan–Meier method, differences were obtained for shock patients at a significance level of 0.083; the number of observations must be doubled to detect statistically significant differences. The final results of hospital mortality require additional in-depth analysis, since in the later stages many deaths were not associated with abdominal sepsis and occurred with already resolved peritonitis. It is necessary to understand to what extent they were associated with experienced sepsis, and to what extent with comorbid pathology; whether there was an association with methods of extracorporeal hemocorrection.